Open innovation in turist family firms: impact of the economic crisis - Soler-Porta, Mariano (My University, 2022)
Given the current situation that we are experiencing in the context of COVID-19, the harshness with which a crisis can hit companies and thus the economy of a country has become clear. Innovation is considered a key element for the survival of companies in the face of an economic crisis. In addition, based on the results observed in the last economic crisis of 2008, we can analyze the effect of innovation (and its different types) on business performance and on the ability of companies to overcome the post-COVID19 economic crisis. The main objective of this research project is to analyze the role of innovation as a determining factor for better business performance in the current COVID-19 context, also analyzing the differential characteristics that family businesses may have and making predictions based on previous crises.
Keywords: Empresas familiares; Innovaciones tecnológicas; Family Firms; Open innovation